(untitled) (مجلة وقف في دراسات الاوقاف, 2026)
Origin of the book: A thesis submitted to obtain a doctorate degree from the Department of Islamic Economics at the Faculty of Sharia at the Islamic University of Madinah The scientific supervisor of the thesis: His Excellency Sheikh Prof. Dr. Saad bin Nasser Al-Shathri This study dealt with the topic of "Waqfs Disputes and their Judicial Applications in the Kingdom of Saudi Arabia". The researcher identified the problem of the study in the lack of clarity of the mechanism for dealing with disputes arising from the establishment and management of the Waqf, the methods of proving them, and the provisions that distinguish them from other disputes. According to this problem, the main question of the study was: What are the substantive and procedural provisions for the disputes of Waqfs and their affiliated entities in the Kingdom of Saudi Arabia? This is a question from which sub-questions emerged, questions about the nature of the Waqf, the concept of dispute in the waqf, the owner of the capacity in its disputes, the types of waqf disputes objectively, the provisions of the disputes of the entities affiliated with the waqf, and the courts competent to consider waqf disputes, the procedures for settling waqf disputes, and the ruling on resorting to alternative means of litigation in waqf disputes.